Ethnoveterinary Use of Plants to Treat Ruminant’s Common Ailments in Rural West Java, Indonesia - Iskandar, Budiawati S.; Mulyanto, Dede; Iskandar, Johan; Kusmoro, Joko (Journal of Tropical Ethnobiology, 2024)
For generations, the inhabitants of rural people of Pasir Putih Village, Rancakalong Subdistrict, Sumedang Regency, West Java, have relied on medicinal plant to maintain the health of their livestock and treat various illness that may distress their livestock. Nowadays, however, the knowledge and practice of livestock treatment using various medicinal plants in rural areas of Pasir Putih Village has tended to eroded, due to the influence of commercial livestock businesses development. Consequently, to treat various livestock, farmers have to buy various modern medicines from the city and the prices are expensive. In addition, the Traditional Ecological Knowledge (TEK), particularly in the young generations has eroded. The aim of this study is to explore and to document the information regarding various ruminant livestock ailments, diversity of plant species used as ethnoveterinary medicine, plant part used and application method applied in treating ruminant ailments, and source of ethnoveterinary medicinal plants in the rural ecosystems of the study area. Method used in this study was mixed-method qualitative and quantitative with an ethnoveterinary medicinal approach. The study resulted showed that during the study recorded 14 common ailments of the ruminants, at least a total of 46 plant species in 41 genera and 17 families were used traditionally and their combination for the treatment of 14 diseases in the study area. Zingiberaceae found to be a dominated family with seven plant species followed by Asteraceae (5 species), Alliacea (5 species), and Fabaceae (5 species). The most commonly used plant parts were leaf (15 species), fruit (11 species), and rhizome (7 species). The wide application of medical plants as the form of drunk (66.67 %), followed by eaten (7.14 %), smeared (7.14 %), and put on (7.14 %). Based on the were the most important medicinal plants used to treat various ruminant ailments Fidelity Level (FL), it was recoded five medical plants, viz., Allium sativum (34.09), Kaempferia galanga (34.09), Zingiber officinale (34.09), Curcuma longa (34.09), and Aloe vera (34.09), in the study area. Regarding source of 46 plant species of ethnoveterinary medical plants was harvested from the homegarden 23 species (50.00 %), garden 11 species (23.91 %), and 12 species (26.05 %) acquired from both homegarden and garden. Thus, the agroecosystem of homegarden and garden are important role not only for the human food production but also livestock feed in the rural ecosystem.